The Importance of Water in the Royal Tradition: a Case Study of the Twelve-Months Royal Ceremonies - สกุลสืบ, ภาณุวัฒน์; สุวรรณประเทศ, อรอุษา (Ganesha Journal, 2018)
An objective of this article was to study an importance of water in a royal ceremony by folklore viewpoint. A scope of the study came from the royal ceremonies in a book titled Twelve-Months Royal Ceremonies written by King Rama V. ‘A rite was a linkage’ was a concept of folklore methodology in 3 dimensions of Kingkeo Attagara. The result found that the royal ceremonies appeared 31 from 57 in the Twelve-month Royal Ceremonies and divided into 2 types; the royal ceremony about water and the royal ceremony used water as a part of rite. Water was so important to the royal ceremony and had a meaning in metaphor as a medium or vehicle to link an individual to the other things that were; 1) the water as a medium to clean a flaw for fortune; 2) the water as a vehicle of linkage between an individual and the deity; and 3) the water as a cross-dimension medium.